Severe hyperandrogenism due to ovarian hyperthecosis in a young woman. Issue 12 (17th December 2019) - Goyal, Alpesh; Malhotra, Rakhi; Kulshrestha, Vidushi; Kachhawa, Garima
Abstract : Hyperandrogenism is a relatively common clinical problem. However, severe hyperandrogenism causing virilisation is rare. A 27-year-old woman presented with generalised hirsutism, clitoromegaly, breast atrophy and secondary amenorrhoea. She had serum testosterone levels elevated to the adult male range. Administration of gonadotropin-releasing hormone (GnRH) analogue resulted in >50% suppression of serum testosterone which was suggestive of luteinising hormone-dependent ovarian hyperandrogenism. Imaging studies of abdomen and pelvis were normal, and ovarian venous sampling failed to show a gradient between the two sides. A presumptive diagnosis of ovarian hyperthecosis was, therefore, considered. Medical treatment with GnRH analogue and combined oral contraceptive pills was initiated to which an excellent clinical and biochemical response was noted. This case highlights a rare presentation of ovarian hyperthecosis in a young woman with severe hyperandrogenism mimicking a virilising neoplasm.